AUTIZM: MUAMMO VA YECHIM - Jumaniyozova, N.R. (SCIENCE and SOCIETY, 2022)
Ensuring the integration of children with autism into society and organizing their edication is one of the most important issues today. This article analyses the psychological and pedagogical basis of the processes carried out with children with autism and their parents.